IT Capability for Health Care Delivery: Is More Better?. (August 2013) - Dey, Asoke; Sinha, Kingshuk K.; Thirumalai, Sriram
In recent years, there has been a proliferation of health information technologies (HITs) that promise to improve the delivery of care. Health care service providers are faced with an increasing push to develop electronic medical record (EMR) capability, which is the ability to leverage health IT to enable and link the clinical processes for an effective and efficient delivery of care. However, there is little guidance in the literature on the performance implications of EMR capability and whether providers should commit to higher stages of EMR capability. Based on data from 1, 011 acute care providers in the United States, the findings of this study suggest that the operational performance of providers, measured as case mix index-adjusted discharges per licensed bed, is positively related to the stage of EMR capability. However, the findings also point to a cautionary insight—committing to higher stages of EMR capability may not be uniformly beneficial to all providers. The findings suggest that the choice of the stage of EMR capability is self-selected. Interestingly, if health care service providers were to be assigned to a higher stage of EMR capability (i.e., incommensurate with their idiosyncratic technological, organizational, and environmental characteristics), the potential operational performance benefit of that stage of EMR capability may remain unrealized.